The insertion loss distribution function of an ear plug, and its implications for the ear plug acceptability - Paolo Lenzuni (Noise and Health, 2020)
Introduction: In order to establish the acceptability of a hearing protector device (HPD) used in a given noisy environment, two key elements must be known with the highest possible accuracy: the insertion loss of the HPD and the associated variability. Methods leading to objective field measurements of insertion loss have become widely available in the last decade and have started to replace the traditional subjective “Real-Ear Attenuation at Threshold” (REAT) laboratory measurements. The latter have long been known to provide a gross overestimate of the attenuation, thus leading to a strong underestimate of the worker’s exposure to noise. Methods: In this work we present objective measurements of the insertion loss of an ear plug, carried out using the E-A-Rfit procedure by 3M on a large sample of 36 female and 64 male subjects. This large number of independent measurements has been exploited to calculate the distribution function of effective noise levels, that is noise levels that take into account the use of the HPD. The knowledge of the distribution function has in its turn allowed the calculation of the uncertainty on the effective noise levels. Results: This new estimate of uncertainty (6 to 7 dB) is significantly larger than most previous estimates, which range between 4 and 5 dB when using objective data but with an improper uncertainty propagation, and around 3 dB when using REAT subjective data. We show that the revised new estimate of uncertainty is much more realistic as it includes contributions that are missed by the other methods. Conclusions: By plugging this revised estimate of uncertainty into the criterion for checking the acceptability of the HPD, a better assessment of the actual protection provided by the HPD itself is possible.